Evaluation and revision of core postoperative nursing outcomes for laryngeal carcinoma in China - Yong-Xia Ding; Hui Yang; Ya-Xuan Sun; Jinxia Xu; Li Jing; Yan Ning; Bin-Quan Wang (BMC, 2021)
Abstract Background The core nursing outcomes for laryngeal carcinoma in China needed further screening and revision. This study aimed to evaluate and revise a questionnaire according to the "Core Nursing Outcomes for Otorhinolaryngology Head-Neck" of the Nursing Outcomes Classification (NOC, 5th Edition), and determine suitable postoperative nursing outcomes for patients with laryngeal carcinoma in China. Methods The commonly used postoperative nursing outcomes for laryngeal carcinoma were screened using a questionnaire given to 93 nurses. An initial expert consultation questionnaire was constructed to discuss the indicators for each nursing outcome. A total of 20 experts were identified using the Delphi method, and their recommendations and revisions on the selected nursing outcomes were collected. Results A total of 14 postoperative core nursing outcomes and 69 indicators were identified for postoperative patients with laryngeal carcinoma, which are subordinate to 4 domains of the NOC: "Physiologic Health", "Psychosocial Health", "Health Knowledge & Behavior", and "Perceived Health". Conclusions The screening and revision of the NOC outcomes and indicators of the Delphi method could be applied to assess the effect of nursing intervention and the quality of the nursing service in China.